A sporadic low‐velocity layer atop the 410 km discontinuity beneath the Pacific Ocean. Issue 7 (4th July 2017) - Wei, S. Shawn; Shearer, Peter M.
Abstract: Waveforms of SS precursors recorded by global stations are analyzed to investigate lateral heterogeneities of upper mantle discontinuities on a global scale. A sporadic low‐velocity layer immediately above the 410 km discontinuity (LVL‐410) is observed worldwide, including East Asia, western North America, eastern South America, the Pacific Ocean, and possibly the Indian Ocean. Our best data coverage is for the Pacific Ocean, where the LVL‐410 covers 33–50% of the resolved region. Lateral variations of our LVL‐410 observations show no geographical correlation with 410 km discontinuity topography or tomographic models of seismic velocity, suggesting that the LVL‐410 is not caused by regional thermal anomalies. We interpret the LVL‐410 as partial melting due to dehydration of ascending mantle across the 410 km discontinuity, which is predicted by the transition zone water filter hypothesis. Given the low vertical resolution of SS precursors, it is possible that the regions without a clear LVL‐410 detection also have a thin layer. Therefore, the strong lateral heterogeneity of the LVL‐410 in our observations suggests partial melting with varying intensities across the Pacific and further provides indirect evidence of a hydrous mantle transition zone with laterally varying water content. Key Points: A sporadic low‐velocity layer immediately above the 410 km discontinuity is observed worldwide The low‐velocity layer covers 33–50% of the resolved region across the Pacific The inferred partial melting above the mantle transition zone shows strong heterogeneities